2016
DOI: 10.1016/j.cej.2016.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of metal-contaminated waste foundry sands using an EDTA–NaOH–NH3 washing solution

Abstract: Waste foundry sand (WFS), which is a hazardous byproduct from the foundry industry, is often contaminated with potentially toxic elements (PTEs), such as Cu, Pb and Zn, and widely re-utilized as a construction material. Therefore, the depollution of WFS has been suggested due to its environment friendly reprocessing to avoid potential long-term hazardous impacts. In the current study, a unique chemically induced technique has been proposed for the removal of PTEs from WFS. EDTA, NaOH and NH 3 were used as extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Similar results were found by Sawai et al [45] that, under acidic conditions, even though the apparent stability constant of Cu-EDTA was greater than that of the corresponding Zn complex under the same pH conditions, the Zn-EDTA was dominant. In order to ensure the cost-effective use of EDTA, it is important to assess the efficacy of metal(loid) removal under different conditions.…”
Section: Co-dissolution Of Major Metal(loid)ssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were found by Sawai et al [45] that, under acidic conditions, even though the apparent stability constant of Cu-EDTA was greater than that of the corresponding Zn complex under the same pH conditions, the Zn-EDTA was dominant. In order to ensure the cost-effective use of EDTA, it is important to assess the efficacy of metal(loid) removal under different conditions.…”
Section: Co-dissolution Of Major Metal(loid)ssupporting
confidence: 90%
“…The most logical explanation for such a difference must be linked to the continued presence of residual EDTA in the two-step extract. Additionally, the stability constants of metal-EDTA varied with the solution pH, which can be confirmed by a the previous research result that Cu-EDTA complexes was a more dominant species than Zn-EDTA in the alkaline pH region [45]. This is an advantage for the two-step process because it means that incorporation of Cu and Zn into the P-precipitate by isomorphic substitution is greatly reduced [48].…”
Section: Experimental Observations After Ph Adjustment With Naohsupporting
confidence: 73%
“…A general low concentration of pesticides, corrosion inhibitors and PAHs was found in the agricultural area indicating a scarce pollution of the river at this point due to agricultural practices. Nevertheless, the relatively high levels of metals such as Ba, Al and Fe indicated a source of industrial contamination (Sawai et al, 2016). In fact, because there is a foundry close to this point, the occurrence of these metals can be ascribed to releases from it.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 20,000 foundries in China, generating 20–30 million tons of foundry waste annually [4]. It was reported that foundry wastes have some application areas, such as fine and/or coarse fillers in concrete, cement production, bricks, embankment material and road bases [5,6,7,8]. However, no more than 15% of foundry waste has been reused in these areas [9].…”
Section: Introductionmentioning
confidence: 99%